Penerapan metode full costing dan variable costing dalam perhitungan biaya produksi pada PT. Fortuna Inti Alam - Anggaria, Astria; Gerungai, Natalia Y. T.; Kalalo, Meily Y. B. (Manajemen Bisnis dan Keuangan Korporat, 2024)
PT. Fortuna Inti Alam is an industrial company in the field of ground coffee. The problem in this study is PT. Fortuna Inti Alam in calculating production costs using the direct costing method. The purpose of this study is to determine the comparison of the full costing method, variable costing and direct costing methods that have been used by the company. The method used in this study is qualitative using primary data. Data collection methods are carried out by observation, interviews, and documentation. The results of the study indicate that the calculation of production costs carried out by PT. Fortuna Inti Alam produces a cost of Rp 2,500,238,866. The calculation of production costs carried out using the full costing method produces a result of Rp 2,720,108,539. The calculation carried out using the variable costing method produces a result of Rp 2,450,388,866. This is because in the calculation of the variable costing method, fixed factory overhead costs are not taken into account.